Analisa Efisiensi Termal Turbin, Kondensor dan Menara Pendingin pada Pembangkit Listrik Tenaga Panas Bumi - Clinton Sihombing (Pusat Pengembangan Sumber Daya Manusia Minyak dan Gas Bumi, 2020)
Geothermal power plants have similarities with other generated power plants such as coal, gas or nuclear power that is converting heat energy into electricity. When the geothermal fluid is extracted from the production well, it will pass through many different processes or equipment on the way to the power plant. During this process the geothermal fluid loses unused energy to generate power. The overall efficiency of the power plant can be affected by several parameters, one of them is design of power plant. This study attempts to analysis the thermal efficiency of the generating components: turbine, condenser and cooling tower at one of geothermal power plant in Indonesia. So, we can know how the performance of the component, whether the component is running well or not. From the calculation results obtained that the turbine, condenser and cooling tower currently still operate well with the value of thermal efficiency of 80%-100%.